Role of fibroblasts in wound healing and tissue remodeling on Earth and in space - Cialdai, Francesca; Risaliti, Chiara; Monici, Monica (Frontiers in Bioengineering and Biotechnology, 2022)
Wound healing and the role fibroblasts play in the process, as well as healing impairment and fibroblast dysfunction, have been thoroughly reviewed by other authors. We treat these topics briefly, with the only aim of contextualizing the true focus of this review, that is the microgravity-induced changes in fibroblasts functions involved in wound healing. Microgravity is a condition typical of spaceflight. Studying its possible effects on fibroblasts and wound healing is useful not only for the safety of astronauts who will face future interplanetary space missions but also to help improve the management of wound healing impairment on Earth. The interesting similarity between microgravity-induced alterations of fibroblast behavior and fibroblast dysfunction in wound healing impairment on Earth is highlighted. The possibility to use microgravity-exposed fibroblasts and wound healing in Space as models of healing impairment on Earth is suggested. The gaps of knowledge on fibroblast functions in wound healing are analyzed. The contribute that studies on fibroblast behavior in weightlessness can make to fill these gaps and, consequently, improve therapeutic strategies, is considered.